Consumer Preference and Willingness to Pay for Organic Broiler Chicken in Jabodetabek - Harmini; Melysa Nabilasari; Yanti Nuraeni Muflikh (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
This study analyzes consumer preferences and Willingness to Pay (WTP) for organic broiler chicken in the Jabodetabek area. The discrete choice experiment (DCE) method analyzes consumer preferences and WTP based on relevant attributes that are in the market or similar to those in the market. The attributes analyzed were organic label, product form, freshness, taste, and price. These five attributes were selected based on a literature review. The study was conducted on 105 respondents who had experience buying and consuming it. Data were collected online from September to October 2024. The results showed that consumers prefer organic broiler chicken with organic labels, cuts/parts, fresh, and tasty. Conversely, high prices can decrease consumers' utility. Consumers are willing to pay IDR Rp96,883/kg more for organic broilers with organic labels, IDR 22,516/kg for cuts/parts, IDR 34,101/kg for fresh, and IDR 70,634/kg for tasty. This study emphasizes the importance of organic certification in increasing consumer confidence and the provision of organic broilers in practical and fresh forms. Producers and marketers are advised to prioritize product quality and convenience and develop marketing strategies highlighting the superior taste and health benefits of this product.